Slope = (y2 - y1) / (x2 - x1)
(-9,6)....x1 = -9 and y1 = 6
(-3,9)...x2 = -3 and y2 = 9
now we sub and solve
slope = (9 - 6) / (-3 - (-9) = 3 / (-3 + 9) = 3/6 = 1/2 <=
Answer:
3x−4y=9 −3x+2y=9
Add these equations to eliminate x: −2y=18
Then solve−2y=18
for y: −2y=18 −2y −2 = 18 −2 (Divide both sides by -2)
y=−9
Now that we've found y let's plug it back in to solve for x.
Write down an original equation: 3x−4y=9
Substitute−9for y in 3x−4y=9: 3x−(4)(−9)=9
3x+36=9(Simplify both sides of the equation)
3x+36+−36=9+−36(Add -36 to both sides)
3x=−27 3x 3 = −27 3 (Divide both sides by 3) x=−9
Answer: x=−9 and y=−9
Hope This Helps!!!
Answer: 4+4=8
Step by step explanation:
I got -648 for the product
here is a contradiction because in one inequality x can be equal to 15 ; and in the other it cannot